The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1021/jp003587c
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Character of the Al2O3(0001)-(√31 × √31)R ± 9° Surface Reconstruction

Abstract: The basal (0001) surface plane of R-Al 2 O 3 has been extensively studied both by experimental techniques and applications of theory. Although this surface is not easily created upon cleavage, it grows in during aluminum oxidation and has been shown to be one of the lowest energy surfaces of alumina. Upon heating under vacuum, this (0001) surface of R-Al 2 O 3 undergoes a series of reconstructions. The final structure obtained at ∼1700 K is an air-stable termination known as the ( 31 × 31)R ( 9°reconstruction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
38
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 49 publications
9
38
0
2
Order By: Relevance
“…The periodic repetitions of the supercell geometry along the z-axis are separated by~12 Å of vacuum to eliminate interactions between periodic cells, and the Al 2 O 3 slab is cut to have an Al truncated surface since it was shown to be the most stable surface termination. [38,44,45] The calculated bulk NiAl lattice constant of 2.891 Å , which is in good agreement with the experimental value of 2.887 Å , yields a lattice misfit of 0.5 pct between NiAl and Al 2 O 3 surfaces, demonstrating a reasonable coherent interface model.…”
Section: Theoretical Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…The periodic repetitions of the supercell geometry along the z-axis are separated by~12 Å of vacuum to eliminate interactions between periodic cells, and the Al 2 O 3 slab is cut to have an Al truncated surface since it was shown to be the most stable surface termination. [38,44,45] The calculated bulk NiAl lattice constant of 2.891 Å , which is in good agreement with the experimental value of 2.887 Å , yields a lattice misfit of 0.5 pct between NiAl and Al 2 O 3 surfaces, demonstrating a reasonable coherent interface model.…”
Section: Theoretical Methodssupporting
confidence: 80%
“…The recent ab initio DFT calculations, [44,45] however, demonstrated that the Al-terminated Al 2 O 3 (0001) surface is more stable than that with O as a termination layer. Therefore, it is essential to investigate the NiAl/Al 2 O 3 interface with Al-terminated layer, at which the highest work of separation can be achieved through examining various translations of NiAl (110) relative to the Al 2 O 3 .…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…1a [25,26]; the Al termination yields non-polar surfaces. Experimentally, it is observed that ð0 0 0 1Þ surfaces prepared at temperatures below $1500 K show a stable ð1  1Þ surface, corresponding to the nonpolar Al-termination; this surface is also characterized by large inward relaxation of the Al atoms [27][28][29][30][31][32]. Annealing to higher temperatures produces a rotated ð ffiffiffiffiffiffi 31 p  ffiffiffiffiffiffi 31 p Þ surface reconstruction, associated with the Al-rich (Al-Al) surface [30,[33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Fig 2͑b͔͒. The metallic-like character of the Al-rich surface of corundum has been reported previously. 33,34 For the reconstructed ͱ31ϫͱ31 surface we would expect the metallization to strongly influence the surface reactivity. For the oxygen terminated surface, on the other hand, the 2p shell could be unfilled.…”
mentioning
confidence: 99%